Atlas of pediatric otolaryngology (W. B. Saunders, 1995)
The book describes the surgical procedures that are performed in infants and children; one such procedure is functional endoscopic sinus surgery. It has included not only the most commonly performed procedures, such as tympanostomy tube insertion and tonsillectomy and adenoidectomy, but also those operations less frequently performed, such as surgical repair of the injured facial nerve and of the auricle for microtia. The wide scope of the chapters' content reflects the diversity of pediatric otolaryngologic surgery today